EFFECT OF AMMONIUM HEXAFLUOROSILICATE ON INHIBITING GROWTH OF VEILLONELLA PARVULA - Annisa, Asby Nia; Andajani, Tutwuri; Sarwono, Agoeng Tjahajani (International Journal of Applied Pharmaceutics, 2017)
Objectives: This study analyzes the effects of ammonium hexafluorosilicate (AHF) on Veillonella parvula. Methods: In this in vitro study, solutions of NaF (25%, 50%, and 100%), AHF (25%, 50%, and 100%), and SDF (38%) were applied to solid medium cultures of V. parvula and Streptococcus mutans. The disc diffusion method was used for testing bacterial sensitivity. Results: AHF was less effective than SDF but more effective than NaF for inhibiting growth of bacteria. Conclusions: AHF could be effective for inhibiting the growth of V. parvula without the side effects of SDF.